2008
DOI: 10.1007/s00520-007-0372-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient–oncologist communication in advanced cancer: predictors of patient perception of prognosis

Abstract: Communication of pessimistic information to patients with advanced cancer increases the likelihood that patients will report concordant prognostic estimates. Communication of optimistic information does not have any direct effect. The best communication strategy to maximize patient knowledge for informed decision making while remaining sensitive to patients' emotional needs may be to emphasize optimistic aspects of prognosis while also consciously and clearly communicating pessimistic aspects of prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 33 publications
3
122
0
1
Order By: Relevance
“…In the present study, the cps was disclosed in only 28% of cases. Many articles suggest that most patients with incurable cancer are keen on receiving information regarding their prognosis [1][2][3]15,16 . Most patients would like to know their predicted survival, although physician and patient predictions are largely discordant 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the cps was disclosed in only 28% of cases. Many articles suggest that most patients with incurable cancer are keen on receiving information regarding their prognosis [1][2][3]15,16 . Most patients would like to know their predicted survival, although physician and patient predictions are largely discordant 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Many cancer patients want to obtain information about their prognosis in a direct and honest manner [1][2][3] . Nevertheless, clinicians are often averse to predicting survival 4 and divulging prognostic information 5 , possibly because breaking bad news to a patient can be stressful for the physician.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that patients' perceptions of disease risks and development influenced their attitude towards treatment preferences, [19] and that an effective communication about prognosis is a prerequisite to define goals of care, making treatment decisions, and planning for the future. [20] This clearly indicates how nourishing the knowledge of cancer patients and enhancing their perception can influence their attitude to communicate such needs to CNCs. Cancer treatments are stressful and their clinical pathway is filled with complications, such as opportunistic infections and medication side effects.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Patients, surrogates, and clinicians filter prognostic information with optimism, limiting effective information sharing. [67][68][69][70] Research is needed to examine new and effective methods to share prognostic information with patients and their families. 4.…”
Section: -31mentioning
confidence: 99%